To transform the equation \(-2y = 14 - 6x\) into slope-intercept form, we want to solve for \(y\) in the form \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept.
Starting with the given equation:
\[ -2y = 14 - 6x \]
First, we can isolate \(y\) by dividing both sides of the equation by \(-2\):
\[ y = \frac{14 - 6x}{-2} \]
Now, we can split the fraction:
\[ y = \frac{14}{-2} - \frac{6x}{-2} \]
This simplifies to:
\[ y = -7 + 3x \]
To express it in slope-intercept form \(y = mx + b\):
\[ y = 3x - 7 \]
So, the equation in slope-intercept form is:
\[ y = 3x - 7 \]
Here, the slope \(m = 3\) and the y-intercept \(b = -7\).